Lack of identification of parameters in a simple behavioral macroeconomic model - Thomas Lux (Kiel University, Department of Economics, 2024)
Identifiability of the parameters is an important precondition for consistent estimation of models designed to describe empirical phenomena. Nevertheless, many estimation exercises proceed without a preliminary investigation into the identifiability of its models. As a consequence, the estimates could be essentially meaningless if convergence to the 'true' parameters is not guaranteed in the pertinent problem. We provide some evidence here that such a lack of identification is responsible for the inconclusive results reported in recent literature on parameter estimates for a certain class of nonlinear behavioral New Keynesian models. We also show that identifiability depends on the subtle details of the model structure. Hence, a careful investigation of identifiability should preceed any attempt at estimation of such models.
Keywords: C53; E12; E32; 330; Behavioral macro; identification; forecast heuristics